MENDETEKSI PENGARUH PASAR MINYAK BUMI DUNIA TERHADAP KRISIS HARGA - Nosami Rikardi (Universitas Bunda Mulia, 2017)
The world oil market, as a result of the convergence of a number of factors, has experienced significant tightness. Some of the factors influencing the market might be temporary, some may be cyclical, and others may possible be permanent. While the high price that resulted from the tight balance between oil demand and supply caused increased energy expenditure for consumer, business, and industry, it also led to higher incomes for energy producer. Expectations concerning future market conditions are quickly embodied in oil price formed in futures market. The fear of geopolitical situations are reflected in price. Speculative buying and selling might also affect prices as financial traders adjust their investment portfolios to reflect expected market conditions. It is possible that the economy as a whole might experience macroeconomic effects, not only from the high oil prices themselves, but as a result of the monetary and fiscal policy responses that might be taken if the prices persist and are determined to constitute inflation.Keywords: Oil price, Demand and supply, Higher incomes, Speculation